The Duchess Countess : the woman who scandalized eighteenth-century London - Ostler, Catherine (Atria Books, 2021)
Elizabeth Chudleigh lived a privileged life in 18th century England where she was part of the Hanoverian court as maid of honor to the Princess of Wales. Known for her style and wit, Elizabeth delighted and scandalized the press and public. She married twice: in secret to a young heir to an earldom and later to a duke. Eventually charged with bigamy, her trial was Georgian England's greatest courtroom spectacle. Yet what should have been her downfall led to greater fame and freedom as she defied society's expectations for women.